EP392 Abdominal radical trachelectomy as a fertility-sparing treatment for early-stage cervical cancer; a single institution experience. (1st November 2019) - Rodolakis, A; Thomakos, N; Theofanakis, C; Haidopoulos, D; Sotiropoulou, M; Bourgioti, C; Moulopoulou, L; Loutradis, D
Abstract : Introduction/Background: The recommended surgical treatment for stages IA2 to IB1 cervical cancer is radical hysterectomy with systematic pelvic lymphadenectomy. However, this approach leads to loss of fertility. Data suggest that abdominal radical trachelectomy (ART) is a feasible alternative that preserves the uterus without increasing the risk of recurrence, preserving the possibility for future childbearing. This study was performed in order to assess the safety of this fertility-sparing approach to early-stage cervical cancer. We present the surgical, oncologic and fertility outcomes of patients treated with ART. Methodology: We conducted a retrospective analysis of patients undergoing fertility-sparing ART at our institution from 2002 to 2016. Results: A total of 84 patients who underwent ART with bilateral systematic pelvic lymhadenectomy were followed for 2–106 months. Thirty-three patients had undergone conization before surgery. The characteristics of the patients include tutor diameter of 8–34 mm (stage IA2=11, stage IB1 [<3.4 mm]=73, average age of 29.5 years (range, 26–43 years), mean operative time of 185 min (range, 142–245 min) and average blood loss of 350 mL (range, 150–750 mL). Uterine arteries were identified at their origin from the internal iliac artery and gently preserved in 80 cases. There were two recurrences in the paraaortic area and one in the remaining part of the cervix. Unfortunately, the last patient developed a kidney metastasis and died of the disease a few weeks later. Forty-eight women attempted to conceive and 35 successful pregnancies were recorded (73%), while 6 of them were preterm (17%). Conclusion: ART can be successfully performed by gynecologic oncologists, who are experienced in radical surgery. It is a safe and well-established procedure with acceptable oncologic and obstetric outcomes, accompanied by low rates of morbidity and mortality. We strongly believe that is mandatory for young women, diagnosed with early-stage cervical cancer, who desire future fertility, to be offered fertility-sparing procedures. Disclosure: Nothing to disclose.